Pengaruh Word of Mouth dan Kualitas Produk terhadap Keputusan Pembelian Kecap Kentjana di Kabupaten Kebumen - Nur Mei Azizah; Erlyna Wida Riptanti; Isti Khomah (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2024)
Kecap Kentjana is the only sweet soy sauce product from Kebumen Regency produced by CV Srikandi Makmur Sejahtera since 1960. Kebumen people who are proud of local products will provide positive recommendations to create a positive reputation for the product. Word of Mouth can significantly increase product awareness and popularity, influencing purchasing decisions for Kecap Kentjana. Apart from Word of Mouth, consumer purchasing decisions are also influenced by price, product quality, and brand image variables. The study aims to determine the effect of these four variables on the purchase decision of Kentjana Soy Sauce in Kebumen Regency. The primary research method uses the descriptive analysis method. The purposive sampling method was used to determine the location. Data were obtained through observation, interviews, and recording using a questionnaire. The purposive sampling method was used to determine the number of samples, with 110 respondents. The Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) approach is used to analyze the data. The results prove that purchasing decisions are significantly influenced by Word of Mouth and product quality. Positive information from someone who is known can encourage potential customers to buy Kentjana soy sauce because potential customers tend to trust recommendations from the closest people, and the quality of the taste offered by Kentjana soy sauce is different from other soy sauce, so purchasing decisions will increase. The results also prove that price and brand image do not significantly influence purchasing decisions. The Kebumen community has consumed Kentjana soy sauce for generations. People have the views and habits of always choosing Kentjana soy sauce as their first choice, so price and brand image variables do not influence purchasing decisions.